2022
DOI: 10.1371/journal.pntd.0009849
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of small intestine bacteria overgrowth and asymptomatic carriage of enteric pathogens in stunted children in Antananarivo, Madagascar

Abstract: Environmental Enteric Dysfunction (EED) refers to an incompletely defined syndrome of inflammation, reduced absorptive capacity, and reduced barrier function in the small intestine. It is widespread among children and adults in low- and middle-income countries and is also associated with poor sanitation and certain gut infections possibly resulting in an abnormal gut microbiota, small intestinal bacterial overgrowth (SIBO) and stunting. We investigated bacterial pathogen exposure in stunted and non-stunted chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…Our work also shows that pathogenic E. coli carriage may be the norm in highly contaminated settings. This is similar to other studies that have reported that a significant proportion of children continue to have sub-clinical pathogen carriage [39][40][41][42]. EPEC, the most detected pathogen, was associated with both acute and chronic inflammation processes.…”
Section: Discussionsupporting
confidence: 90%
“…Our work also shows that pathogenic E. coli carriage may be the norm in highly contaminated settings. This is similar to other studies that have reported that a significant proportion of children continue to have sub-clinical pathogen carriage [39][40][41][42]. EPEC, the most detected pathogen, was associated with both acute and chronic inflammation processes.…”
Section: Discussionsupporting
confidence: 90%
“…SIBO was assessed by culture as described in ref. 15 DNA Extraction and Sequencing. Samples were extracted by commercial kits (QiaAmp cador Pathogen Mini or cador Pathogen 96 QIAcube HT Kit; Qiagen) following the manufacturer's recommendations with an additional bead-beating step to increase mechanical disruption.…”
Section: Methodsmentioning
confidence: 99%
“…S8). To this purpose, we tested lipid uptake in murine small intestinal cells (m-IcCl2) exposed to a subset of clinical small intestinal isolates representing the main small intestinal taxa recovered (SI Appendix, Table S5) (15). All oral bacterial strains tested with the exception of Lactobacillus paracasei, a reference strain that showed no change in lipid absorption in previous work (12), significantly decreased 14 C-oleic acid absorption in m-IcCl2 cells compared with control conditions (Fig.…”
Section: Ectopic Colonization With Small Intestinal Isolates Of Oral ...mentioning
confidence: 99%
“…Bands of elevated prevalence were predicted to the immediate north of the Congo basin and Great Lakes region, just to the north of the Tropic of Capricorn, and in tropical coastal West Africa, consistent with the high rates reported in studies not included in this analysis, such as in the Central African Republic 69 , Guinea Bissau 70 , Mozambique 64 and Madagascar. 71 Zones of high predicted prevalence also occurred in South America, Caribbean Central America, the Ganges–Brahmaputra Delta, and New Guinea among others, and may reflect the secondary influence of static environmental and household-level risk factors. These findings should inform the design and selection of sites for forthcoming phase 3 Shigella vaccine trials 21 , and populations living in these hotspots should be considered high priority for eventual vaccine rollout campaigns.…”
Section: Discussionmentioning
confidence: 99%